PERAN KELUARGA DALAM MENINGKATKAN MINAT KUNJUNGAN LANSIA KE POSYANDU LANSIA DI KEPENGHULUAN BANGKO BAKTI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Susi Fatimah; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The increasing number of elderly population each year, the government has made many policies for elderly health services with the formulation of the elderly posyandu that aimed at improving health for every elderly. Various roles and support from family is needed in increasing  the interest of elderly visit so that life of the elderly becomes more qualified and prosperous. This research examined the role of the family in increasing interest of elderly to visit elderly posyandu in Kepenghuluan Bangko Bakti, Kecamatan Bangko Pusako, Rokan Hilir Regency that aims to find out the role of familiy in increasing  the interest of the elderly to join the elderly posyandu. This research used descriptive quantitative research method. The population in this research were family who lived with the elderly totaling 150 respondents. A purposive sampling technique is used to determine the sample of the research. There were 60 respondents participating in this research. To collect the data, the researcher used observation technique, questionnaire and documentation. From the result of the study of 60 respondents, most of them have a good family support role in increasing the interest in visiting elderly posyandu. The conclusion is that the roles of support, both emotional support, wife support, information support and family assesment support in increasing the interest of elderly visit to posyandu, are good.  Facing for every health worker and every elderly posyandu cadre who works in order to further enhance and develop activities that held in the elderly posyandu, and for each elderly familiy it is expected to share roles and tasks with other family member to increase interest in elderly to visit the elderly posyandu. Keywords: Family Role, Elderly Posyandu